Standardised Nomenclature, Abbreviations, and Units for the Study of Bone Marrow Adiposity: Report of the Nomenclature Working Group of the International Bone Marrow Adiposity Society - Bravenboer, Nathalie; Bredella, Miriam A.; Chauveau, Christophe; Corsi, Alessandro; Douni, Eleni; Ferris, William F.; Riminucci, Mara; Robey, Pamela G.; Rojas-Sutterlin, Shanti; Rosen, Clifford; Schulz, Tim J.; Cawthorn, William P. (Frontiers in Endocrinology, 2020)
Research into bone marrow adiposity (BMA) has expanded greatly since the late 1990s, leading to development of new methods for the study of bone marrow adipocytes. Simultaneously, research fields interested in BMA have diversified substantially. This increasing interest is revealing fundamental new knowledge of BMA; however, it has also led to a highly variable nomenclature that makes it difficult to interpret and compare results from different studies. A consensus on BMA nomenclature has therefore become indispensable. This article addresses this critical need for standardised terminology and consistent reporting of parameters related to BMA research. The International Bone Marrow Adiposity Society (BMAS) was formed in 2017 to consolidate the growing scientific community interested in BMA. To address the BMA nomenclature challenge, BMAS members from diverse fields established a working group (WG). Based on their broad expertise, the WG first reviewed the existing, unsystematic nomenclature and identified terms, and concepts requiring further discussion. They thereby identified and defined 8 broad concepts and methods central to BMA research. Notably, these had been described using 519 unique combinations of term, abbreviation and unit, many of which were overlapping or redundant. On this foundation a second consensus was reached, with each term classified as “to use” or “not to use.” As a result, the WG reached a consensus to craft recommendations for 26 terms related to concepts and methods in BMA research. This was approved by the Scientific Board and Executive Board of BMAS and is the basis for the present recommendations for a formal BMA nomenclature. As an example, several terms or abbreviations have been used to represent “bone marrow adipocytes,” including BMAds, BM-As, and BMAs. The WG decided that BMA should refer to “bone marrow adiposity”; that BM-A is too similar to BMA; and noted that “Ad” has previously been recommended to refer to adipocytes. Thus, it was recommended to use BMAds to represent bone marrow adipocytes. In conclusion, the standard nomenclature proposed in this article should be followed for all communications of results related to BMA. This will allow for better interactions both inside and outside of this emerging scientific community.